2014
DOI: 10.1016/j.jmb.2013.09.037
|View full text |Cite
|
Sign up to set email alerts
|

Novel Interaction of Ornithine Decarboxylase with Sepiapterin Reductase Regulates Neuroblastoma Cell Proliferation

Abstract: Ornithine decarboxylase (ODC) is the sentinel enzyme in polyamine biosynthesis. Both ODC and polyamines regulate cell division, proliferation, and apoptosis. Sepiapterin reductase (SPR) catalyzes the last step in the biosynthesis of tetrahydrobiopterin (BH4), an essential cofactor of nitric oxide synthase (NOS), and has been implicated in neurological diseases but not yet in cancer. In this study, we present compelling evidence that native ODC and SPR physically interact, and we defined the individual amino ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 58 publications
(87 reference statements)
2
33
1
Order By: Relevance
“…Zhao et al (2008) found that ODC was highly expressed at the implantation site in the mouse uterus during the peri-implantation period. There exists well-documented literature about AOZS as negative feedback control regulators of cellular polyamine content (Lange et al 2014). The OAZ2 gene expressed in the prehierarchical follicles had the tendency of decliningrising-declining-rising presenting W-shaped pattern in changes.…”
Section: Resultsmentioning
confidence: 97%
“…Zhao et al (2008) found that ODC was highly expressed at the implantation site in the mouse uterus during the peri-implantation period. There exists well-documented literature about AOZS as negative feedback control regulators of cellular polyamine content (Lange et al 2014). The OAZ2 gene expressed in the prehierarchical follicles had the tendency of decliningrising-declining-rising presenting W-shaped pattern in changes.…”
Section: Resultsmentioning
confidence: 97%
“…Previous reports have illustrated that SPR functions as regulator in NB [12][13][14] . However, the role of SPR in HCC has not been reported as far as we know.…”
Section: Discussionmentioning
confidence: 95%
“…In addition, it has been reported that BH 4 plays a key role in the growth, angiogenesis, and migration of tumors [8][9][10] . Sepiapterin reductase (SPR), which is an important regulator in the biosynthesis of BH 4 11 , has been demonstrated to be significantly correlated with survival of human neuroblastoma (NB) 12 . Although NB cells treated with SPR small interfering RNA (siRNA) or an enzymatic inhibitor showed a significant decrease in growth, the underlying mechanism has not been fully elucidated [12][13][14] , and the biological functions and molecular mechanisms of SPR in most types of tumors remain unknown.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations